A Modular Solder System with Hierarchical Morphology and Backward Compatibility. Issue 33 (18th July 2018) - Lee, Han Bit; Kim, Young Won; Kim, Sang Hoon; Park, Suk Hee; Choi, Joon‐Phil; Aranas, Clodualdo
Abstract: A modular solder system with hierarchical morphology and micro/nanofeatures in which solder nanoparticles are distributed on the surface of template micropowders is reported. A core–shell structure of subsidiary nanostructures, which improved the intended properties of the modular solder is also presented. In addition, polymer additives can be used not only as an adhesive (like epoxy resin) but also to impart other functions. By combining all of these, it is determined that the modular solder system is able to increase reflowability on a heat‐sensitive plastic substrate, oxidation resistance, and electrical conductivity. In this respect, the system could be readily modified by changing the structure and composition of each constituent and adopting backward compatibility with which the knowledge and information attained from a previously designed solder can offer feedback toward further improving the properties of a newly designed one. In practice, In–Sn–Bi nanoparticles engineered on the surface of Sn–Zn micropowders result in pronounced reflowing on a flexible Au‐coated polyethylene terephthalate (PET) substrate even at the low temperature of 110 °C. Depending on their respective concentrations, the incorporation of CuO@CeO2 nanostructures and poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) polymers increases oxidation resistance and electrical conductivity of the modular solder. Abstract : The modular solder system consists of template micropowders with strong mechanical strength, solder nanoparticles with different melting temperatures, subsidiary nanostructures added for a specific intention, and polymer additives mainly as an adhesive prior to reflowing but also to perform other important functions. The modular solder bumps were consolidated on a Au‐coated PET substrate at 110 °C, remaining undamaged after bending.